2020
DOI: 10.1101/2020.05.27.119255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Head-to-head comparison of four antigen-based rapid detection tests for the diagnosis of SARS-CoV-2 in respiratory samples

Abstract: 21In the context of the Covid-19 pandemic, the development and validation of rapid and easy-to-22 perform diagnostic methods are of high priority. We compared the performance of four rapid 23 antigen detection tests for SARS-CoV-2 in respiratory samples. Immunochromatographic SARS-24CoV-2 assays from RapiGEN, Liming bio, Savant, and Bioeasy were evaluated using universal 25 transport medium containing naso-oropharyngeal swabs from suspected Covid-19 cases. The 26 diagnostic accuracy was determined in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 23 publications
8
46
1
5
Order By: Relevance
“…The copyright holder for this preprint this version posted October 6, 2020. ; https://doi.org/10.1101/2020.10.04.20206466 doi: medRxiv preprint 6 with automated reading (BioEasy), which demonstrated sensitivities of 100% for samples with Cts ≤ [6,7] and of 98% for samples with Cts ≤ [21]. In contrast, immunochromatographic SARS-CoV-2 antigen tests demonstrated lower sensitivity values of 74%-85% for samples with Cts ≤ 25 [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 6, 2020. ; https://doi.org/10.1101/2020.10.04.20206466 doi: medRxiv preprint 6 with automated reading (BioEasy), which demonstrated sensitivities of 100% for samples with Cts ≤ [6,7] and of 98% for samples with Cts ≤ [21]. In contrast, immunochromatographic SARS-CoV-2 antigen tests demonstrated lower sensitivity values of 74%-85% for samples with Cts ≤ 25 [7,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Immunochromatographic assay is the most commonly used method for the detection of SARS-CoV-2 antigens [74,75]. Thomas et al compared four lateral flow antigen-detection kits (RapiGEN, Liming bio, Savant, and Bioeasy) for the detection of SARS-CoV-2 and showed test performances with significant differences.…”
Section: Antigen Tests For Diagnosis Of Covid-19mentioning
confidence: 99%
“…Among these tests, the Bioeasy test showed the highest accuracy of 89.2% and Kappa coefficient of 0.8, while Liming bio test was discontinued during testing because of poor performance. Sensitivities of other kits ranged from 16.7% for the Savant assay to 85% for the Bioeasy test [75].…”
Section: Antigen Tests For Diagnosis Of Covid-19mentioning
confidence: 99%
“…Such challenges have affected the clinical sensitivity of antigen tests for influenza and other respiratory viruses [112]. Recent studies on four different commercial antigen tests demonstrated a wide range of sensitivities from 16.7 to 85% (with 100% specificity) in COVID-19 clinical samples [113]. Other studies have shown sensitivity as high as 93.9% (CI 95%: 86.5-97.4).…”
Section: Antigen Detectionmentioning
confidence: 99%